The Relationship Between Anxiety Levels and Family Support and UKMPPD Results at The Faculty of Medicine, University of Muhammadiyah Semarang - Kamila Kamila; Mega Pandu Arfiyanti; Andra Novitasari; Muslimah Muslimah (International Journal of Health and Pharmaceutical (IJHP), 2025)
The Medical Profession Program Student Competency Test (UKMPPD) is a test and assessment on a national scale for students of the medical profession program, which emphasizes attitudes, knowledge, and skills as a basis for practicing medicine. Based on data from the UKMPPD National Committee and Institutional Feedback, the UKMPPD results at Muhammadiyah University Semarang, the percentage of UKMPPD pass in February 2021 and November 2021 were 75% and 81.25%, respectively. In general, the level of anxiety experienced while undergoing medical education has a negative impact, namely students having difficulty undergoing competency assessment and can reduce their level of confidence when they are about to face exams. In addition to anxiety, it was also identified that influenced the UKMPPD results, including family support. This study aims to analyze the relationship between anxiety levels and family support with UKMPPD outcomes. This study used a quantitative method in the form of analytic observational with a cross sectional approach. This study used the Hamilton Rating Scale for Anxiety questionnaire and the family support questionnaire. The sample in this study were medical professional education students at the Faculty of Medicine, University of Muhammadiyah Semarang who took part in UKMPPD for the November 2022 period. Sampling used a total sampling technique. The results of the univariate analysis with a total of 32 respondents, namely the majority had high family support (71.9%), a mild level of anxiety (50.0%), the majority were female (86.8%), and the majority of respondents graduated UKMPPD (87.5%). The results of the chi square analysis of the anxiety level variable had a value of p = 0.008 (p < 0.05), and the family support variable was p = 0.557 (p > 0.05). There is a significant relationship between the level of anxiety with UKMPPD results. Family support has no significant relationship with UKMPPD results.